2001
DOI: 10.4049/jimmunol.167.9.4887
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Ryanodine Receptor Isoforms in Immune Cells

Abstract: Ryanodine receptor (RYR) is a Ca2+ channel that mediates Ca2+ release from intracellular stores. We have used RT-PCR analysis and examined its expression in primary peripheral mononuclear cells (PBMCs) and in 164 hemopoietic cell lines. In PBMCs, type 1 RYR (RYR1) was expressed in CD19+ B lymphocytes, but less frequently in CD3+ T lymphocytes and in CD14+ monocytes. Type 2 RYR (RYR2) was mainly detected in CD3+ T cells. Induction of RYR1 and/or RYR2 mRNA was found after treatment with stromal cell-derived fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 28 publications
3
85
0
1
Order By: Relevance
“…Jurkat cells express RyR1 according to an earlier study elucidating the expression of RyR isoforms in immune cells (32). It was found that 4-chloro-m-cresol, a specific activator of RyR1, induced Ca 2ϩ release, thereby confirming functional expression of RyR in Jurkat cell lines.…”
Section: Expression and Purification Of Cytosolic Ryr1 Proteins And Cmentioning
confidence: 81%
“…Jurkat cells express RyR1 according to an earlier study elucidating the expression of RyR isoforms in immune cells (32). It was found that 4-chloro-m-cresol, a specific activator of RyR1, induced Ca 2ϩ release, thereby confirming functional expression of RyR in Jurkat cell lines.…”
Section: Expression and Purification Of Cytosolic Ryr1 Proteins And Cmentioning
confidence: 81%
“…We have previously shown that in Jurkat T cells, the RyR regulate SOCE by controlling Ca 2ϩ store refilling (19). However, the conclusions drawn from studies on Jurkat T cells cannot be extended to primary human T cells because the latter express type 1 RyR (RyR1) and type 2 RyR (RyR2), whereas Jurkat T cells express type 3 RyR (RyR3) (25). Furthermore, T cell lines are not representative of any functional state typical of primary T cells and do not respond to stimulation in the same manner as primary T cells.…”
mentioning
confidence: 83%
“…Type 1 ryanodine receptor (RyR1) predominates in skeletal muscle but is expressed at lower levels in other tissues (3)(4)(5)(6)(7)(8)(9). In skeletal muscle, RyR1 is located in the junctional terminal cisternae of the SR, where it assembles in ordered orthogonal arrays.…”
mentioning
confidence: 99%